The impact of an online job fair: Experimental evidence from Bangladesh - Norihiko Matsuda; Ryotaro Hayashi (Asian Development Bank (ADB), 2023)
Online job fairs are a new labor market intervention. This paper provides the first experimental evidence on their impact by evaluating an online fair for information and communication technology jobs in Bangladesh. The fair generated a non-negligible number of job offers; however, over 90% of them were rejected, so no effect on employment probability or type was found. Interestingly, jobseekers lowered their reservation wages, kept their jobs longer, and ended up in worse skill-matched jobs. The reason is that jobseekers initially had overoptimistic expectations, but learned about market conditions at the fair, lowered their expectations, and became discouraged from job search. As a result, those who had already been employed kept their jobs longer, even if the jobs did not match their skills, and those who had initially been unemployed ended up with lower employment probabilities and lower skill-match quality.
Keywords: O12; O15; J24; J64; 330; job fair; job matching; online search; youth employment; Bangladesh